Autalia villosa, a new species from Korea, and an annotated catalog of the genus Autalia Leach (Coleoptera: Staphylinidae: Aleocharinae) - Park, Jong-Seok; Ahn, Kee-Jeong (Zootaxa, 2005)
A new species, Autalia villosa Park & Ahn (type locality: Mt. Seoraksan, Gangwon Prov., Korea), is described from Korea. An illustration of the habitus and line drawings of diagnostic characters are presented. An annotated world catalog of the genus Autalia Leach is provided.